Peran dukungan sosial dalam mengurangi distress emosional pasca putus cinta - Asrofi, Nur-muchamad_ Muchamad (Maliki Interdisciplinary Journal, 2026)
This study aims to understand the role of social support in reducing emotional distress in young adults experiencing heartbreak. Using a qualitative approach with an intrinsic case study design, the study involved two participants aged 18 to 25 years who had experienced heartbreak in the last 3 to 12 months. Data were collected through in-depth interviews and analysis using Braun & Clarke’s Thematic Analysis (2006). The results showed that emotional distress after a breakup manifested in the form of deep sadness, anxiety, loss of motivation, and impaired academic functioning in one of the participants. Social support plays an important role in the process of emotional recovery through three main functions: (1) emotion regulation through the opportunity to talk and be listened to without judgment, (2) the reformation of cognitive perspectives through constructive advice, and (3) the provision of a secure base that replaces the lost attachment figure. The most influential sources of social support came from family (especially mothers), friends who provided empathetic responses, and interviewers who created emotionally safe spaces. This study has implications for practitioners, educational institutions, and society to improve understanding of effective and emotionally sensitive forms of social support.